inSOA: uma linguagem de composição de serviços para dispositivos móveis - Barcelos, Giovane Oliveira de (Universidade do Vale do Rio do Sinos, 2009)
Services composition on mobile devices is becoming essential for current and future needs of IT users. These needs are supported by the convergence from centralized to distributed architectures that encourage the web services composition. These web services, motivated by the Web Services architecture, soon evolved into an SOA. This architecture in turn, in the services orchestration, has required composition language for their effective implementation. These languages, has advanced to interpreted and declarative languages. In this evolution context, this work presents, a declarative language of services composition services called inSOA. This language was developed to execute on mobile devices as part of a project of a collaborative ubiquitous architecture called USOA. InSOA is a solution focused on Web Services and SOA adherent to the patterns of services composition, and can be embedded in a language of general purpose and light in the better DSL languages style. As a way to test and evaluate the langu
Keywords: composição de serviços; computação móvel; DSL; linguagem de composição de serviços; linguagem de domínio específico; SOA; domain-specific language; language of services composition; mobile devices; services composition; Ciências Exatas e da Terra